2017
DOI: 10.3389/fpls.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field Seems to Not Influence Transcription via CTCT Motif in Three Plant Promoters

Abstract: It was proposed that magnetic fields (MFs) can influence gene transcription via CTCT motif located in human HSP70 promoter. To check the universality of this mechanism, we estimated the potential role of this motif on plant gene transcription in response to MFs using both bioinformatics and experimental studies. We searched potential promoter sequences (1000 bp upstream) in the potato Solanum tuberosum and thale cress Arabidopsis thaliana genomes for the CTCT sequence. The motif was found, on average, 3.6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Biological processes are currently being monitored under the influence of static magnetic field (SMF) and alternating MF, the value of which is several orders larger than the Earth’s MF (Sztafrowski et al 2017). In vitro, SMF exposure can reduce the number of viable cells in melanoma, ovarian carcinoma, and lymphoma cell lines (Raylman et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Biological processes are currently being monitored under the influence of static magnetic field (SMF) and alternating MF, the value of which is several orders larger than the Earth’s MF (Sztafrowski et al 2017). In vitro, SMF exposure can reduce the number of viable cells in melanoma, ovarian carcinoma, and lymphoma cell lines (Raylman et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of GWAS-based CGs in maize ear-related organs and developmental stages indicated that these genes could have an influence on the accumulation of assimilates in the grain, among which were phenolic compounds critical for resistance to storage pests such as MW [ 89 , 114 , 115 ]. In agreement with the negative interaction between plant biotic and abiotic stress responses resulting from negative cross-talk between absicic acid (ABA) and the jasmonic acid (JA), salicylic acid (SA), and ethylene (ET) signaling pathways [ 108 , 109 , 110 , 112 , 116 , 117 ], most of the CGs were upregulated and downregulated under biotic and abiotic stress conditions, respectively. In vivo expression analyses under local conditions would help to confirm the role of these CGs in maize response to FAW, SB, and MW.…”
Section: Discussionmentioning
confidence: 88%
“…The genomic and functional information related to most of these CGs, the conserved domains within their protein sequences, and genetic descriptions of their co-expressed rice and arabidopsis orthologs suggest their possible involvement in plant defense mechanisms. Functional features known for their involvement in both biotic and abiotic plant response such as WRKY, F-BOX, NAM, bZIP, LRR, AUX_IAA, zf-C2H2, DNA, ATP, ion, protein-binding protein domains, MADS-box, C2C2-YABBY, MYB transcription factors, calcium-related transmembrane transport elements, protein kinases, oxydoreduction activities, and several binding factors [ 108 , 109 , 110 , 111 , 112 , 113 ] characterized most of the CGs, making them promising genetic factors for the regulation of plant response to insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ELF MF exposure to the seeds right from the beginning to the seedling stage resulted in enhanced growth. The New developments in this field are focused on the genetic transformations or epigenetic regulations playing their role in the growth promoting effects of EMFs on plant growth and its development (Rammal et al ., 2014;Sztafrowski et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%